1989
DOI: 10.1128/mcb.9.12.5424
|View full text |Cite
|
Sign up to set email alerts
|

CBP2 protein promotes in vitro excision of a yeast mitochondrial group I intron.

Abstract: The terminal intron (b12) of the yeast mitochondrial cytochrome b gene is a group I intron capable of self-splicing in vitro at high concentrations of Mg2+. Excision of b12 in vivo, however, requires a protein encoded by the nuclear gene CBP2. The CBP2 protein has been partially purified from wild-type yeast mitochondria and shown to promote splicing at physiological concentrations of Mg2+. The self-splicing and protein-dependent splicing reactions utilized a guanosine nucleoside cofactor, the hallmark of grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 45 publications
0
45
0
Order By: Relevance
“…In principle, disruption of COB and COX1 mRNA maturation would lead to respiratory deficiency, but the stability of the mitochondrial genome should not be affected. There are several examples of nuclear-encoded factors involved in the splicing of COB and/or COX1 introns, such as Mss18p (Seraphin et al 1988), Mrs1p (Bousquet et al 1990), or Cbp2p (Gampel et al 1989), and while they are required for respiratory competence in strains containing their target introns, their dysfunctions do not lead to the loss of mtDNA integrity. An interesting exception is the NAM2 gene, which encodes the mitochondrial leucyl-tRNA synthetase, which is also a splicing factor for the excision of several group I introns (Labouesse et al 1985;Labouesse 1990), but in this case, it is the function in mitochondrial translation that is essential for the integrity of the mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, disruption of COB and COX1 mRNA maturation would lead to respiratory deficiency, but the stability of the mitochondrial genome should not be affected. There are several examples of nuclear-encoded factors involved in the splicing of COB and/or COX1 introns, such as Mss18p (Seraphin et al 1988), Mrs1p (Bousquet et al 1990), or Cbp2p (Gampel et al 1989), and while they are required for respiratory competence in strains containing their target introns, their dysfunctions do not lead to the loss of mtDNA integrity. An interesting exception is the NAM2 gene, which encodes the mitochondrial leucyl-tRNA synthetase, which is also a splicing factor for the excision of several group I introns (Labouesse et al 1985;Labouesse 1990), but in this case, it is the function in mitochondrial translation that is essential for the integrity of the mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…It self-splices at high MgClz concentration in vitro, whereas splicing under physiological conditions requires CBP2. a protein known to be required for splicing in vivo (McGraw and Tzagoloff 1983;Gampel and Tzagoloff 1987;Partono and Lewin 1988;Gampel et al 1989). Kinetic analysis of the protein-free and protein-facilitated reactions has revealed that splicing is accelerated three orders of magnitude by saturating CBP2 protein at SmMMgCl, (Weeks and Cech 1995a).…”
Section: Protein Facilitationmentioning
confidence: 99%
“…Excision of some intervening sequences also depends on nuclear genes such as CBP2, and SUV3 and MSS116, the latter two coding for RNA helicases (3,21,22). Cbp2p interacts with and stabilizes a splicing competent secondary structure of the cytochrome b pre-mRNA (23). Suv3p has been implicated in stabilizing the COX1 transcript by regulating turnover of group I intronic RNAs (24,25), whereas Mss116p has been shown to function in splicing of all mtDNA introns in S. cerevisiae and Neurospora crassa (26).…”
mentioning
confidence: 99%